Pendampingan Peningkatan Pengetahuan dan Keterampilan Manajemen Keperawatan di Rumah Sakit PKU Muhammadiyah Sampangan - Arum Pratiwi; Abi Muhlisin; Muzakar Isa; Dian Hudiyawati; Dimas Ria Angga Pribadi; Nabila Novita Priyani; Alya Fitri Dwi Karunia (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Introduction: Health services at PKU Muhammadiyah Sampangan Hospital require nurses to have good nursing management skills, but initial survey results show that there are still limitations in knowledge and skills in the areas of case rounds, conferences, patient classification, leadership, and communication using the ISBAR format. Objective: to improve nurses' knowledge and skills through a nursing management training and mentoring program. Methods: The program was conducted in 14 sessions using lectures, interactive discussions, case simulations, role plays, and live demonstrations in the treatment room. Evaluation was conducted using pre-tests and post-tests to measure changes in participants' abilities. Results: The program showed an increase in average knowledge in all aspects, including case rounds (59.77 to 69.09), ISBAR (81.43 to 90.00), conferences (95.91 to 98.18), leadership (73.68 to 85.53), and patient classification (82.63 to 91.42). Conclusion: This activity demonstrated that training and mentoring are effective in improving the nursing management competencies of nurses. Therefore, it is recommended that this activity be carried out continuously to support the quality of service and professionalism of nursing practice in hospitals